Post-translational modifications in health and disease - Vidal, Cecilio J.; SpringerLink (Online service). (New York Springer, 2011)
Post-translational modifications serve many different purposes in a wide variety of cellular processes,such as protein synthesis, folding, stability, the housing of prosthetic groups, vesicular trafficking,protein targeting to particular cell stores, exocytosis and endocytosis, the biogenesis of cell organelles and basal lamina. Signal transduction, with functional effects for enzyme regulation and metabolic control on the one hand, and gene expression, cell division, differentiation and apoptosis on the other, is also prominent. Post-translational Modifications in Health and Disease provides the reader with nineteen reviews that stimulate further investigations in the proteomic field - focusing on functional and pathological aspects of protein prenylation, the incorporation of glycosylphosphatidylinositol (GPI) moieties, oxidation, nitrosylation, glycosylation, and phosphorylation and dephosphorylation - with emphasis on their outcome for protein-protein interaction phenomena and down-stream effects. Additional chapters are devoted to protein ubiquitination, sumoylation and endoplasmic reticulum-associated degradation (ERAD), the influence of histone modification on gene expression and DNA repair, and proteolytic processing of intracellular and basal lamina proteins. This book will be of particular significance to researchers, clinicians, and students of biology, pharmacy and medicine.
Isoprenoid Modifications -- GPI-Anchored Proteins in Health and Disease -- Protein Oxidation -- Involvement of S-Nitrosylation in Neurodegeneration -- Protein Glycosylation, and Congenital Disorders of Glycosylation -- Defective Glycosylation of Dystroglycan in Muscular Dystrophy and Cancer -- Protein kinase A: The Enzyme and Cyclic AMP Signaling -- The Protein Kinase C Family: Key Regulators Bridging Signaling Pathways in Skin and Tumor Epithelia -- Maintaining Energy Balance in Health and Disease: Role of AMP-activated Protein Kinase -- Protein Phosphatases in the Brain: Regulation, Function and Disease -- Covalent Protein Modification as a Mechanism for Dynamic Recruitment of Specific Interactors -- Regulation of Gene Expression by the Ubiquitin-Proteasome System and Implications for Neurological Disease -- Small Ubiquitin-like Modifiers and other Ubiquitin-like Proteins -- ER-associated Degradation and its Involvement in Human Disease: Insights from Yeast -- Regulation of Chromatin Structure and Transcription via Histone Modifications -- Chromatin: the Entry to and Exit from DNA Repair -- Poly(ADP-rybosyl)ation of Chromosomal Proteins: Epigenetic Regulation and Human Genomic Integrity in Health and Disease -- Post-translational Proteolytic Processing on Intracellular Proteins by Cathepsins and Cystatins -- Metalloproteases and Proteolytic Processing.
Electronic reproduction.
Keywords: Post-translational modification; Natural history; Electronic books